The diversity of maternal-age effects upon pre-adult survival across animal species. Issue 1932 (12th August 2020) - Ivimey-Cook, Edward; Moorad, Jacob
Abstract : Maternal senescence is the detrimental effect of increased maternal age on offspring performance. Despite much recent interest given to describing this phenomenon, its distribution across animal species is poorly understood. A review of the published literature finds that maternal age affects pre-adult survival in 252 of 272 populations (93%) representing 97 animal species. Age effects tended to be deleterious in invertebrates and mammals, including humans, confirming the presence of senescence. However, bird species were a conspicuous exception, as pre-adult survival tended to increase with maternal age in surveyed populations. In all groups, maternal-age effects became more negative in older mothers. Invertebrates senesced faster than vertebrates, and humans aged faster than non-human mammals. Within invertebrates, lepidopterans demonstrated the most extreme rates of maternal-effect senescence. Among the surveyed studies, phylogeny, life history and environment (e.g. laboratory versus wild populations) were tightly associated; this made it difficult to make confident inferences regarding the causes of diversity for the phenomenon. However, we provide some testable suggestions, and we observe that some differences appear to be consistent with predictions from evolutionary theory. We discuss how future work may help clarify ultimate and proximate causes for this diversity.